Essays on the economics of bioenergy and emissions trading. - Moon, Jin-Young (My University, 2012)
The three essays in this dissertation focus on the economics of bioenergy and emissions trading. Chapter Two analyzes the economic impacts of cellulosic feedstock production in a major watershed of south-central Minnesota. A regional economic model of agricultural production in the watershed is constructed. By integrating environmental parameters from a biophysical simulation analysis of the watershed, the model focuses on economic and environmental issues associated with increasing use of two cellulosic feedstocks, corn stover and switchgrass, at the watershed level. Results indicate that corn stover can be produced at a relatively low marginal cost compared to switchgrass. Sediment and nutrient losses from corn stover production make switchgrass more promising on environmental grounds but the high marginal cost of production causes switchgrass to cover only small part of crop land if farmers have unrestricted choice about how to supply cellulosic feedstocks. Chapter Three extends the model of chapter Two to examine the tradeoffs between cellulosic feedstock production and water quality by analyzing policy options targeted to address those tradeoffs. Policy alternatives considered include restrictions on total nitrate-N load in the watershed and production subsidies for switchgrass – an energy crop with potential environmental benefits. Restricting nitrate-N loads increases the cost of cellulosic feedstock supply and in some circumstances makes switchgrass production an economical alternative. Switchgrass production subsidies, if sufficiently high can increase feedstock supply while reducing or eliminating the negative effects of feedstock production on water quality. Chapter Four examines how uncertainty in emissions affects firms’ decision of permit purchase and abatement. This paper extends previous models of emissions trading by considering uncertainty as well as the order of firms’ decisions about abatement and permit trading. When there is uncertainty about emissions, total expected emissions are the same regardless of the order of moves. The results show that whether firms abate more under uncertainty is dependent on the expected penalty cost and marginal abatement cost. If the expected marginal penalty cost is greater than the marginal abatement cost, the firm will choose to reduce emissions and abate more under uncertainty. When expected penalty is greater than marginal cost of abatement, increase in uncertainty makes expected emissions decrease given unit penalty fee.
University of Minnesota Ph.D. dissertation. June 2012. Major: Applied Economics. Advisors: Jeffrey Apland and Stephen Polasky,. 1 computer file (PDF); ix, 133 pages, appendices A-C.
Keywords: Cellulosic Feedstock; Emissions trading; Uncertainty; Water Quality; Watershed; Applied Economics